Critical thinking for strategic intelligence - Pherson, Katherine Hibbs (Sage, CQ Press, 2021)
Klappentext: "With Critical Thinking for Strategic Intelligence, Katherine Hibbs Pherson and Randolph H. Pherson have updated their highly regarded, easy-to-use handbook for developing core critical thinking skills and analytic techniques. This indispensable text is framed around 20 key questions that all analysts must ask themselves as they prepare to conduct research, generate hypotheses, evaluate sources of information, draft papers, and ultimately present analysis, including: How do I get started? Where is the information I need? What is my argument? How do I convey my message effectively?"--